The Influence of Farmer Entrepreneurial Behavior on Shallot Farming Performance - Adetya, Aulia; Rachmina, Dwi; Lukman Mohammad Baga (Jurnal AGRISEP, 2025)
Shallot farming has the main characteristic of being season-dependent. The phenomenon of shallot production scarcity in central areas generally occurs during the off-season, when production is 30% lower compared to the in-season. Human resource development is a key factor in facing this challenge. Globalization demands creative and innovative farmers to thrive and compete. The role of entrepreneurial behavior in the agricultural sector is essential to create more innovative, independent, and risk-taking farmers in managing their farms. This research aimed to (1) examine how individual characteristics and the business environment influence the entrepreneurial behavior of shallot farmers and (2) assess the influence of this entrepreneurial behavior on the performance of shallot farming. This study employed SEM-PLS (Structural Equation Modeling) using the Partial Least Squares (PLS) approach for data analysis, with a total sample of 130 respondents. The results showed that individual characteristics and the business environment positively and significantly influence entrepreneurial behavior, which in turn positively affects shallot farming performance. The improvement of farmers' entrepreneurial behavior is influenced by internal factors (individual characteristics) and external factors (business environment), yet the ability to grow and take risks remains a weak indicator. Building capacity through training and gaining access to low-interest financing (KUR) can help farmers overcome challenges. Additionally, low farming commitment due to unstable farmer incomes can be addressed through price stabilization programs, such as partnerships to ensure market access with consistent selling prices. Future research is recommended to explore strategies for enhancing farm performance through factors beyond entrepreneurial behavior.